Experimental insights into mucilage-mediated nutrient diffusion in different soil textures - Bahareh Hosseini; Meysam Cheraghi; Daniel Sebastian Moser; Maire Holz; Valerie Pusch; Rainer Remus; Mohsen Zarebanadkouki (Plant and Soil, 2026)
Background and Aims Volumetric soil water content ( $${θ }_{v}$$ θ v ) strongly regulates nutrient diffusion, particularly under drying conditions. This study investigates how plant-derived mucilage alters water retention and the effective diffusion coefficient ( $${D}_{s}$$ D s ) of calcium (Ca 2 ⁺) in soils with contrasting textures (sand, sandy loam, and loam) under varying $${θ }_{v}$$ θ v . Methods We amended soils with maize mucilage at contents ( $${C}_{m}$$ C m ) of 0.0, 2.5, 5.0, and 7.5 mg/g adjusted them to three $${θ }_{v}$$ θ v levels. A 45 Ca tracer and phosphor imaging were used to track Ca 2 ⁺ diffusion over time. $${D}_{s}$$ D s was estimated from the 45 Ca distribution, allowing evaluation of mucilage effects on water retention and solute transport. Results Mucilage effects were strongly texture- and $${θ }_{v}$$ θ v -dependent. In loam, mucilage enhanced $${θ }_{v}$$ θ v and $${D}_{s}$$ D s at the same soil matric potential ( $${ψ }_{soil}$$ ψ soil ); for example, at a $${θ }_{v}$$ θ v of 0.125 cm 3 /cm 3 ( $${ψ }_{soil}$$ ψ soil = $$-$$ - 23,608 cm), $${D}_{s}$$ D s increased by more than eightfold at the $${C}_{m}$$ C m of 7.5 mg/g compared to the control. This was attributed to increased water retention and improved liquid connectivity. In sandy soil, mucilage increased $${θ }_{v}$$ θ v only at higher content but decreased $${D}_{s}$$ D s due to an increased liquid viscosity, which impeded solute mobility. Sandy loam showed intermediate behaviour. Conclusion Mucilage modulates both soil water retention and nutrient diffusion in a texture-dependent manner. Its beneficial effects are most pronounced in finer-textured soils, while coarser soils require higher mucilage contents to observe similar improvements.

Mobilization of Readily Exchangeable Organic P – A Potential Driver of Enhanced P Acquisition Efficiency in Upland Rice - Eva Mundschenk; Rainer Remus; Matthias Wissuwa; Christiana Staudinger; Uxue Otxandorena-Ieregi; Eva Oburger; Maire Holz (Journal of Soil Science and Plant Nutrition, 2025)
High phosphorus (P) fixation in soils is a major constraint on crop production worldwide. To address this challenge, we investigated plant-induced changes in soil P pools, aiming to identify superior P uptake strategies by examining whether different upland rice genotypes access various P sources in the rhizosphere. Two genotypes (DJ123 and Nerica4) with varying P acquisition efficiencies (PAEs) were grown in an Andosol under low- and high-P fertilization. Fertilizer-P was labeled with 33P, and plants were harvested 34 days after emergence. Hedley fractionation was conducted on initial soil, as well as on bulk and rhizosphere soils after harvest, to analyze changes in fertilizer/native soil and inorganic/organic P in different fractions. Fertilizer-P entered all Hedley fractions, with the largest share being found in the moderately labile (NaOH-P, + 72%) and stable (H2SO4-P, + 19.8%) P fractions under both P treatments. The plant presence resulted in a decrease in fertilizer-P in the most labile P fraction (resin-P), whereas native soil-P and organic P increased in the other labile P fraction (NaHCO3-P). Moreover, a sharp decline in organic NaOH-P fraction in the rhizosphere, along with an increase in inorganic NaOH-P under both P conditions, was observed. Genotypic differences were evident, with DJ123 exhibiting increased organic resin-P concentrations in the rhizosphere compared to Nerica4. DJ123 demonstrated superior access to readily exchangeable organic P in the rhizosphere, highlighting a potential driver for its enhanced PAE. These findings emphasize the importance of genotype-specific strategies for optimizing P mobilization and acquisition in highly P-fixing soils.

Impact of Erosion-Induced Topsoil Dilution on Rapeseed Root Growth, Assimilate C Input, and Turnover in the Soil - Ayten Pehlivan; Julian Ruggaber; Rainer Remus; Jürgen Augustin; Steffen Kolb (Journal of Soil Science and Plant Nutrition, 2025)
This study investigates the impact of soil erosion-induced topsoil dilution by subsoil admixture on the input and turnover of recently assimilated carbon (C) in soil during crop growth. A pot experiment was conducted with three admixture levels (0%, 12%, and 24%) of subsoil (Bt material) mixed into topsoil (Ap material) of an eroded Nudiargic Luvisol. Spring rapeseed ( Brassica napus L.) plants were grown in pots under controlled conditions. Plants were pulse-labelled with 14 CO 2 at the stem elongation growth stage, and the distribution of assimilated 14 C in the plant soil system was determined 21 days after labelling. With increasing topsoil dilution, C inputs from root biomass and rhizodeposition increased. Despite higher assimilate respiration, more assimilate C remained in the soil. The highest proportion of retained assimilate C was found in the particulate organic matter (POM) fraction (43–50%), followed by the mineral-associated organic matter (MAOM) (41–45%) and dissolved organic carbon (DOC) (5–13%) fractions. Increasing subsoil admixture increased the proportion of assimilate C in the POM fraction while reducing it in the DOC, with no effect on the MAOM fraction. Topsoil dilution by subsoil incorporation can indeed increase the supply of assimilate C to the soil in the form of roots and rhizodeposits. However, as the proportion of stabilized assimilate C in the MAOM fraction did not increase during the short study period, an erosion-induced decrease in soil organic carbon (SOC) stocks can only be compensated over several years by increased sequestration of assimilate C in the soil.

Simulated soil erosion predominantly affects fungal abundance in the rapeseed rhizosphere - Julian Ruggaber; Ayten Pehlivan; Rainer Remus; Davide Francioli; Stephan Wirth; Jürgen Augustin; Steffen Kolb (Rhizosphere, 2024)

Fertilizer Addition Modifies Utilization of Different P Sources in Upland Rice on Strongly P-fixing Andosols - Eva Mundschenk; Rainer Remus; Jürgen Augustin; Matthias Wissuwa; Christiana Staudinger; Eva Oburger; Eckhard George; Maire Holz (Journal of Soil Science and Plant Nutrition, 2024)
Aims High Phosphorus (P) efficiencies such as internal P utilization efficiency (PUE) and P acquisition efficiency (PAE) are crucial for upland rice production, particularly on highly P-fixing soils like Andosols. While the effect of root traits associated with high PAE in upland rice has been studied intensively, less attention has been given to the origin of P (native soil-P versus fertilizer-P) taken up by plants when evaluating differences in P efficiency. Here we aim to evaluate the efficiency of different upland rice genotypes to acquire native soil-P and fertilizer-P. Methods Four upland rice genotypes with varying PAE were grown in an Andosol at low- and high-P fertilization level and harvested 9 and 34 days after emergence. Fertilizer-P was labeled with 33 P to distinguish between the efficiency to acquire P originating from native soil and fertilizer by measuring plant P uptake. Results Increased fertilizer supply enhanced native soil-P uptake. Under low-P conditions the genotype DJ123 showed a superior PAE and an increased acquisition of native soil-P while AB199 was identified to have a superior internal PUE under P deficient conditions. Differences between genotypes in overall PAE under high-P conditions were not significant but the distinction of P sources showed that genotype DJ123 acquired significantly more native soil-P per unit root than all other genotypes. Conclusions Our results indicate that variations in PAE among genotypes are associated with their ability to access native soil-P. DJ123 emerged as the most adept genotype in acquiring sparingly soluble native soil-P and future studies should unravel the rhizosphere processes underlying increased PAE of native soil-P.

Root but not shoot litter fostered the formation of mineral-associated organic matter in eroded arable soils - Eva Kaštovská; Michal Choma; Gerrit Angst; Rainer Remus; Jürgen Augustin; Steffen Kolb; Stephan Wirth (Soil and Tillage Research, 2024)

What regulates the rhizodeposition of winter oilseed rape during growth? - Rainer Remus; Divya Pandey; Dietmar Lüttschwager (Plant and Soil, 2022)
Purpose The goal of this work was to contribute to a better understanding of the process of rhizodeposition in crops and to find helpful approaches for creating a simple model of rhizodeposition. For this purpose, we tested three hypotheses about the relationships and changes in the relative C partitioning coefficients and their ratios. In particular, we analyzed the relationships between root growth, belowground respiration, rhizodeposition and other traits during plant growth. Methods The ranges of variation in $$^{14}$$ 14 C partitioning coefficients and various plant traits were determined after $$^{14}$$ 14 C labeling of four winter oilseed rape genotypes in three developmental stages. Result For all genotypes, we found very strong and significant correlations between the percentages of freshly assimilated C used for rhizodeposition and root growth. In addition, we showed that the ratios of the relative $$^{14}$$ 14 C fluxes in the root-soil-soil gas system changed significantly during plant development and that the relative and absolute C fluxes of rhizodeposition followed different trends. The root growth rate and the change in the ratio of the percentages of $$^{14}$$ 14 C in rhizodeposition and root tissue over time were the key factors that determined the absolute amount of rhizodeposited C. We also found that the C partitioning in a taproot system leading to root growth and rhizodeposition was similar to that of an adventitious root system. Conclusion Based on our results, we conclude that using the identified key factors in combination with a root growth model, a simple model can be generated to describe rhizodeposition.

Demonstration of the rapid incorporation of carbon into protective, mineral-associated organic carbon fractions in an eroded soil from the CarboZALF experimental site - Rainer Remus; Michael Kaiser; Markus Kleber; Jürgen Augustin; Michael Sommer (Plant and Soil, 2018)

Dynamic linking of 14C partitioning with shoot growth allows a precise determination of plant-derived C input to soil - Rainer Remus; Jürgen Augustin (Plant and Soil, 2016)

Determining the timepoint when 14C tracer accurately reflect photosynthate use in the plant-soil system - Rainer Remus; Katja Hüve; Jürgen Pörschmann; Jürgen Augustin (Plant and Soil, 2016)

The contribution of Phragmites australis litter to methane (CH4) emission in planted and non-planted fen microcosms - Sari Juutinen; Tuula Larmola; Rainer Remus; Edith Mirus; Wolfgang Merbach; Jouko Silvola; Jrgen Augustin (Biology and Fertility of Soils, 2003)